Recycling of fishpond wastewater by adsorption of pollutants using aged refuse as an alternative low-cost adsorbent - Anijiofor, Sandra Chinenyenwa; Nik Daud, Nik Norsyahariati; Idrus, Syazwani; Che Man, Hasfalina (BMC, 2018)
The waste to wealth initiative has been championed by many researchers through the use of waste materials as adsorbents for wastewater treatment. The aged refuse became a research interest due to its availability, low cost and adsorption capacity. The aged refuse used was collected from the Air Hitam Sanitary Landfill site in Selangor, Malaysia which is more than 8 years of placement. The material characterization showed characteristics such as high porosity (51%), bulk density (ρ), 1.23 g cm−3, total surface area (Brunauer–Emmett–Teller) of 3.376 m2 g−I, capacity for exchange of cations and organic content of 9.90% which are ideal conditions for adsorption. The optimized operating conditions during treatment were dosage of 2 g 100 mL−1, pH 6, particle size ≤ 2 mm, agitation speed 250 rpm, and contact time of 70 min. The results showed maximum reduction efficiency of 91% for Chemical oxygen demand, Total suspends solids and Total dissolved solids and 84, 88 and 95% for Biochemical oxygen demand, and Colour respectively and over 60% removal was observed in 10 min. Freundlich model was used to test the experimental data and it gave good correlation with R2 values very close to 1. The aged refuse technology is suitable for wastewater recovery and reuse through innovative column based aged refuse biofilter which incorporates adsorption, filtration, biodegradation and sedimentation processes.